# Math

posted by .

## Similar Questions

1. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
2. ### Math

1. Explain the advantages and disadvantages of both the substitution method and the elimination method for solving a system. Help please. The only reasons I can think of is because in substitution it might be more difficult cause there's …
3. ### math

Solve by elimination method. 2r-5s=-33 5r+2s=48 Solve by substitution method. 5x+6y=5 x-9y=40 I always get these two confused... can someone please help me with these two problems?
4. ### math

Solve by elimination method. 2r-5s=-33 5r+2s=48 Solve by substitution method. 5x+6y=5 x-9y=40 I always get these two confused... can someone please help me with these two problems?

6. ### math substitution method

use the substitution method to solve 7x+5y=-26 x=28-6y
7. ### substitution method

Solve by substitution method please help me solve this. I do not know how to do this at all. The question is 3x+8y=33 and x=31-6y I know that I have to plug x into the first x like 3(31-6y)+ 8y = 33 but i do not know what to do from …
8. ### Algebra 1

bobpursey, In this problem you helped me with earlier: Solve using any appropriate method. y = 2× - 5, y = ½× + 1 Substitution, substitute for y. 2×-5=½ × + 1 3/2 x=6 x=4 y= 2*4-5=3 How did you choose which method you were going …
9. ### Math

17) solve this linear system using the method of substitution. 2y-x=-10 y= -3/2x-1 20) simplify then solve by substitution 2(x-4)+y=6 3x-2(y-3)=13 just need help with these 2.